Contact dermatitis to methylisothiazolinone - Maria Antonieta Rios Scherrer; Vanessa Barreto Rocha; Ana Regina Coelho Andrade (Sociedade Brasileira de Dermatologia, 2015)
Abstract: Methylisothiazolinone (MI) is a preservative found in cosmetic and industrial products. Contact dermatitis caused by either methylchloroisothiazolinone/methylisothiazolinone (MCI/MI or Kathon CG) or MI has shown increasing frequency. The latter is preferably detected through epicutaneous testing with aqueous MI 2000 ppm, which is not included in the Brazilian standard tray. We describe a series of 23 patients tested using it and our standard tray. A case with negative reaction to MCI/MI and positive to MI is emphasized.